Optimizing Analog Identification and Evaluation in the OECD QSAR Toolbox to Enable Robust Read-Across - E. Byrd; C. Albertson; P. Kern; L. Reinsalu; J. Rose; G. Yan; X. Zhang; C. Lester (Regulatory Toxicology and Pharmacology, 2026)

Measuring changes in environmental radiological background from construction of an advanced nuclear reactor testing facility - Jim Drachenberg; James E. Johnstone; Gage McClaine; Rusty S. Towell; Jared Barker; Neddy Chepkoech; Dale Cox; John C. Dalton; T.L. Head; Timothy J. Kennedy; Kim L. Pamplin; Jackson Shoultz; et al. (Journal of Environmental Radioactivity, 2026)

Identifying the impact of primary production pathways and mixotrophs on energy flow in a tributary backwater of the world’s largest reservoir - Patrick J. Pickett; Lei Zhang; Georgia K. Dwyer; Ashley Macqueen; Rebecca E. Lester (Ecological Modelling, 2026)

Temperature- and species-specific infection could modify stream insect communities - Sarah A. Taig; Galen Holt; Georgia K. Dwyer; Rebecca E. Lester (Current Microbiology, 2026)
To maintain diverse communities under changing environmental conditions, species must be able to concentrate density feedback within species compared to between species. Density feedback can occur via multiple mechanisms, including predator partitioning, and is often mediated by the physical environment. If species respond differently to the environment (e.g. susceptibility to predators changes under different conditions) then environmental fluctuations can provide the necessary separation of density feedback to promote coexistence. Additionally, directional change in environmental conditions (as with climate change) can yield overall shifts in community composition. We assess possible pathways that a fungal-like parasite ( Saprolegnia spp.) could modify these effects in a community of Hydrobiosidae caddisflies. We exposed caddisfly egg masses from four species to four controlled temperature regimes in the laboratory and determined mortality from infection. Saprolegnia spp. infection in caddisfly egg masses is species specific, a signature for predator partitioning which can influence coexistence. The caddisfly species also differ in how temperature alters their infection rates, with dramatic shifts in relative infection rates depending on the duration and timing of periods of high temperature. Our findings suggest that Saprolegnia spp. infection could limit dominant species, shift community composition, and help stabilise coexistence under fluctuating temperatures. While we show key conditions of coexistence are met, quantifying the effect of these temperature-mediated infection rates would require measuring the extent to which they modify density-dependent feedback.

Macroinvertebrate community changes in response to riparian revegetation activities and land cover using historical datasets - Mariah J. Sampson; Kay Critchell; John Gooderham; Ty G. Matthews; Rebecca E. Lester (Science of The Total Environment, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Perinatal exposure to delta-9-tetrahydrocannabinol (THC) alters goal-directed behavior and dopamine functioning in wistar rats - Monica S. Carbajal; Rebecca C. Crenshaw; Victoria E. Williams; Laura G. Billings; Chelsea M. Dixon; Deranda B. Lester; Helen J. K. Sable (Psychopharmacology, 2026)
Rationale Cannabis use during 2021pregnancy is common as many pregnant women consider cannabis as a safe way to alleviate symptoms associated with pregnancy because it is “natural”. However, clinical evidence links perinatal cannabis exposure to externalizing behavior in offspring. In preclinical research, most studies focus on exposure to the psychoactive constituent of cannabis, delta-9-tetrahydrocannabinol (THC). THC is lipophilic, allowing it to cross the placental barrier and be secreted in maternal milk, thereby exposing the fetus/neonate. Objective We used operant procedures to measure motivation and impulsivity in adult offspring perinatally exposed to THC. Methods Dams were orally exposed to 0 or 5 mg/kg/day THC daily from 14 days prior to breeding to postnatal day (PND) 14. Differential reinforcement of high rates (DRH) and differential reinforcement of low rates (DRL) of responding tasks were used to examine motivation and impulsive action. We also measured dopamine (DA) functioning in the medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) via in vivo fixed potential amperometry in littermates of rats that completed behavioral testing. Results Perinatal THC exposure had minimal effects on impulsive action measures during DRL 15s. Rather, perinatal THC exposure decreased DRL 15s burst responses and completed trials in both sexes, and reinforcers earned in THC-exposed males. Decreased lever presses during DRH were observed in both sexes perinatally exposed to THC, as well as fewer reinforcers in THC-exposed males. THC exposure did not alter baseline DA release in the NAc or mPFC, but did attenuate the dopaminergic response to cocaine in the NAc. Conclusions These results suggest perinatal exposure to THC can decrease motivation to work for reinforcers during high-effort tasks, that this effect may be more pronounced in males, and that the “amotivational state” resulting from perinatal THC exposure may be due to reinforcer devaluation. Keywords : oral THC, developmental neurotoxicology, amotivational syndrome, mesocorticolimbic dopamine.

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Streptococcus dysgalactiae From Farm‐Raised Channel Catfish in Mississippi, USA, With Notes on Fish‐Associated Group C S. dysgalactiae - Sujita Balami; Lester H. Khoo; Caitlin E. Older; Geoffrey C. Waldbieser; Alvin C. Camus; Taylor I. Heckman; Cynthia C. Ware; Bradley M. Richardson; John P. Hawke; Adrián López‐Porras; Esteban Soto; Craig A. Shoemaker; et al. (Journal of Fish Diseases, 2025)
Lancefield serological group C Streptococcus dysgalactiae (GCSD) is an emerging cause of fish disease worldwide, largely associated with mariculture in Asia. In the United States (US), GCSD had been a pathogen of minimal concern for fish, but recent cases indicate a putative emergence in wild and cultured freshwater fish populations in the Americas. The current study discusses three novel cases of GCSD‐associated streptococcosis in US farm‐raised channel catfish ( Ictalurus punctatus ) occurring in Mississippi, US, in 2022 and 2023. Infected fish presented with pendulous abdomens, red swollen vents, and petechiae on the mouth, fins and ventral lateral abdomen. Clinical isolates were cultured from the kidney and brain and initially confirmed as GCSD by 16S rRNA gene sequencing, followed by phylogenetic analyses using the superoxide dismutase gene ( sod A), 16S/23S internal transcribed spacer region and nine genes within a multilocus sequence analysis scheme for piscine pathogenic Streptococcus . Catfish GCSD were highly homologous to fish strains from published reports from Asia and South America, forming a discrete phylogenetic clade, separate from human and other terrestrial animal isolates. Pairwise genomic comparisons suggest this fish‐associated group does not belong to any currently recognised subspecies and may represent a unique subtype. The broadening host and geographic range of GCSD, coupled with the evidence of a discrete aquatic lineage and recent reports from freshwater fishes in the southeastern US, suggest GCSD is a potential emergent threat to catfish aquaculture in the US.

Insights on the roles of women in effective and procedurally just environmental governance from coastal fisheries management in Fiji - Caroline E. Ferguson Irlanda; Sangeeta Mangubhai; Elisabeta Waqa; Hugh Govan; Arundhati Jagadish; Sarah E. Lester; Morena Mills; Margaret Tabunakawai‐Vakalalabure; Alifereti Tawake; Tanya O'Garra (Conservation Biology, 2025)
Conservationists and fisheries managers have historically focused somewhat narrowly on achieving environmental goals at the expense of environmental justice. We examined the links between the two in the context of coastal fisheries management in Fiji, a nation highly dependent on marine resources and with significant external conservation investment. We focused on procedural justice, an underexamined dimension of environmental justice, which is concerned with how decisions are made and by whom. We took an intersectional approach in that we considered individuals’ multiple and interacting social identities with a focus on the roles of women. We examined the barriers to and benefits of women's and men's participation in fisheries management. We surveyed 655 key informants in 146 villages and conducted talanoa sessions (a Fijian research method) and 54 semistructured interviews in 4 of those villages. Women's participation was associated with numerous ecological and social benefits and an increase in support for fisheries management, yet their participation was very low. Women were more knowledgeable than men about the ocean, there was broad support for women's participation, and women's participation was critical for maintaining their access to fishing areas. However, restrictive gender norms and roles often limited women to token participation or no participation. This was especially true for young women and women who married into the village. Local women and men identified pathways to increasing women's participation, including the important role men can play in supporting women's voices. More generally, our results highlight the interconnection between achieving conservation and environmental goals and improving procedural environmental justice.

Mariculture Narratives in Climate Change Research and Policy: Alignment, Mismatch, and Opportunities for a Climate‐Resilient Industry - Elizabeth O. Ruff; Lillian M. Bradshaw; Sarah E. Lester (Reviews in Aquaculture, 2025)
Like other sectors of our global food system, marine aquaculture (mariculture) is threatened by a myriad of stressors resulting from a changing climate. Increasing attention has been given to the impact of these stressors on mariculture across a variety of taxonomies and geographies. Alongside this perspective of mariculture as vulnerable to climate change impacts, another narrative has also emerged framing mariculture as a potential mitigation and adaptation measure against climate change. Here, we evaluate the scope and context of these differing narratives across the peer‐reviewed literature and how they are reflected in national mariculture and climate change policy across 31 representative countries. Our literature review identifies a strong research bias toward mariculture being impacted by climate change (75%), with a similar trend present across the small number of relevant policies. While there is broad narrative alignment between science and policy at a global level, in comparing country‐level case studies to their corresponding national policies, we find that five countries have no alignment between research and policy with respect to individual climate change stressors; though most countries have at least some degree of alignment. Strategic governance is a critical tool for responding to climate change and has been shown to play a significant role in shaping the marine aquaculture industry. Our analysis highlights a pattern of science and policy mismatch that could lead to missed opportunities to leverage mariculture's potential as a climate change mitigation and adaptation tool as well as bolster the industry's resilience to climate impacts.

HydroBOT: an integrated toolkit for assessment of hydrology-dependent outcomes - Galen Holt; Georgia K. Dwyer; David Robertson; Martin Job; Rebecca E. Lester (Environmental Modelling & Software, 2025)

Quantification and attribution of spectral variation in irrigated perennial tree crops - James Malcher; David Robertson; Galen Holt; Rebecca E. Lester (Remote Sensing Applications: Society and Environment, 2025)

Dietary Iron Fortification Did Not Affect the Intestinal Microbiome for Channel Catfish ( Ictalurus punctatus ) Juveniles, but Decreased Their Resistance Against Edwardsiella ictaluri - Fernando Y. Yamamoto; Caitlin E. Older; Lester H. Khoo; Nicholas Romano; Bradley M. Richardson; Brian D. Ott; David J. Wise; Cynthia Ware; Penelope M. Goodman; J. Grant Reifers; Matt J. Griffin (Journal of Fish Diseases, 2025)

Livelihood diversity and fishing skill during COVID-19 lockdowns in French Polynesia - Matthew Lauer; Jean Wencélius; Paige Dawson; Sally J. Holbrook; Sarah E. Lester; Scott D. Miller; Shannon Nelson-Maney; Andrew Rassweiler; Russell J. Schmitt (Frontiers in Marine Science, 2024)
Small-scale fisheries provide seafood for billions of people and are one of the largest employers in many coastal communities. Those households engaged in these fisheries who maintain diverse income sources are generally thought to be better prepared to cope with social or ecological perturbations such as the crises presented by the COVID-19 pandemic. One outcome of the COVID-19 crisis was the collapse of international tourism after many nations instituted strict border controls to slow the virus’s spread, severely impacting coastal communities that depend on tourism-related employment. This research assessed the effects of COVID-19-induced collapse of tourism on small-scale coral reef fishers and households in Moorea, French Polynesia. Ninety-five households were surveyed about their livelihoods, fishing, demographics, and income-generating occupations before and after the lockdown. Shifts in fish biomass were evaluated using time series data collected through underwater visual surveys, and roadside fish vendors were surveyed to assess fish sales. Results showed that after tourism employment evaporated more Moorea households began fishing to boost their incomes and food security. However, the increase in fishing pressure showed no appreciable decline in the biomass of fishable species. The households responsible for the increased fishing activities were those who were working in the tourism economy prior to the pandemic and subsequently lost their jobs. Households that combined fishing with construction or other stable sectors showed greater abilities to cope, while those combining fishing with tourism were heavily impacted. Importantly, results showed that those households devoted solely to fishing managed the crisis adeptly due to their superior fishing skills and ecological knowledge. This pattern suggests that not all forms of household livelihood diversification confer equal advantages and that resource-dependent households are not necessarily intrinsically less resilient. More generally, it is argued that we should be cautious when promoting livelihood diversification as a blanket solution to decrease household vulnerability, and that ecological knowledge diversity is underappreciated.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

When does place attachment lead to climate change adaptation and when does it not? A quantitative review and thematic analysis - D.Y. Jayakody; V.M. Adams; G. Pecl; E. Lester (Environmental Science & Policy, 2024)

Leaving seafood on the table: Pilot pathways a missed opportunity for U.S. mariculture - Elizabeth O. Ruff; Sarah E. Lester (Marine Policy, 2024)

A flexible consistent framework for modelling multiple interacting environmental responses to management in space and time - Galen Holt; Ashley Macqueen; Rebecca E. Lester (Journal of Environmental Management, 2024)

Further investigation into the impact of manuring on stable carbon (δ13C) and nitrogen isotope (δ15N) values in pulses: a four-year experiment examining Celtic bean (Vicia faba) - Edward R. Treasure; Darren R. Gröcke; Jonathan J. Lester; Rosie R. Bishop; Samuel E. Jackson; Mike J. Church (Archaeological and Anthropological Sciences, 2024)
Plant stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope values can be used to directly investigate crop husbandry practices such as manuring; a key variable in understanding the scale and intensity of past farming practices. We present new results from a four-year experiment examining the impact of manuring on the δ 13 C and δ 15 N values of a heritage cultivar of the broad or faba bean ( Vicia faba ), the ‘Celtic black broad bean’. This paper builds upon our previous pilot study (Treasure ER, Church MJ, Gröcke DR (2016) The influence of manuring on stable isotopes (δ 13 C and δ 15 N) in Celtic bean ( Vicia faba L.): archaeobotanical and palaeodietary implications. Archaeol Anthropol 8:555–562. https://doi.org/10.1007/s12520-015-0243-6 ). Our results indicate that manuring increased δ 15 N values in beans, with a mean value of 0.5 ± 0.4‰ in control samples compared to a mean value of 2.1 ± 1.3‰ in the most intensively manured plots. It was not always possible to distinguish between an unmanured and manured crop on the basis of δ 15 N values, although manured crops consistently exhibited larger variation in δ 15 N. Bean δ 13 C values show no clear relationship with manuring, although large variability (> 3‰) was found within crops cultivated under the same conditions. Manuring also increased plant biomass production, seed-size and the bean per plant ratio. Overall, we suggest that high δ 15 N values (> 1.5‰) in archaeobotanical remains of pulses can be attributed to small-scale, intensive cultivation that is typical of gardens where manuring rates are very intensive.

Internal organs and body tissues of free-swimming whale sharks (Rhincodon typus) imaged using underwater ultrasound - M. G. Meekan; F. Thompson; K. Brooks; R. Matsumoto; K. Murakumo; E. Lester; A. Dove; B. Hopper (Frontiers in Marine Science, 2024)
Ultrasound imaging can be used as an effective tool to measure the reproductive status and condition of sharks. This usually requires restraint of the subject, which is not feasible in the wild when the target species is of conservation concern and very large, as is the case for whale sharks. Our study invoked a behavioral response in free-swimming whale sharks that allowed snorkelers to image internal organs and structures using a submersible ultrasound scanner linked to an iPhone in an underwater housing. We were able to reliably locate and monitor the heart and other internal organs inside the body cavity, structures inside the head, and image skin and muscle in the dorsal surface of the sharks. The technique is evaluated as a means for assessing the condition and reproductive status of free-swimming whale sharks.

Associations between neighborhood characteristics and child well-being before and during the COVID-19 pandemic: A repeated cross-sectional study in the Environmental influences on Child Health Outcomes (ECHO) program - Xueying Zhang; Courtney K. Blackwell; Janet Moore; Shelley H. Liu; Chang Liu; Christopher B. Forrest; Jody Ganiban; Annemarie Stroustrup; Judy L. Aschner; Leonardo Trasande; Sean C.L. Deoni; Amy J. Elliott; et al. (Environmental Research, 2024)

Contributions by extreme rain events to long-term hyperarid landscape evolution - Lester Olivares; Teresa E. Jordan (Quaternary Science Reviews, 2024)

Can freshwater plants and algae act as an effective feed supplement to reduce methane emissions from ruminant livestock? - Rebecca E. Lester; Ashley Macqueen; Emily K. Armstrong; David T. Dodemaide; Georgia K. Dwyer; Thomas S. Mock; Stephanie Payne; Michael Smith; Michaela Storen; Lawrence Webb (Science of The Total Environment, 2024)

The role of marine aquaculture in contributing to the diversity and stability of U.S. seafood production - Sarah E. Lester; Rebecca R. Gentry; Halley E. Froehlich (Marine Policy, 2024)

What makes a place special? Understanding drivers and the nature of place attachment - D.Y. Jayakody; V.M. Adams; G. Pecl; E. Lester (Applied Geography, 2024)

How wide, how much? A framework for quantifying the economic and ecological outcomes of altering riparian width on agricultural land - James Malcher; Kay Critchell; Ty G. Matthews; Rebecca E. Lester (Science of The Total Environment, 2023)

Seagrass ecosystem services show complex spatial patterns and associations - Jennifer McHenry; Andrew Rassweiler; Sarah E. Lester (Ecosystem Services, 2023)

Geographic variation in organic carbon storage by seagrass beds - Jennifer McHenry; Andrew Rassweiler; Gema Hernan; Alexandra K. Dubel; Carolyn Curtin; Jakob Barzak; Nicholas Varias; Sarah E. Lester (Limnology and Oceanography, 2023)
Since seagrasses are efficient sinks for marine organic carbon, there is growing interest in incorporating seagrass protection and restoration into climate mitigation schemes, that is, offering credit for accumulated carbon to offset carbon dioxide emissions. However, patterns and drivers of organic carbon storage by seagrasses are not well resolved, especially at scales relevant to management decisions. Here, we quantified geographic variation in standing stocks of sedimentary organic carbon (Mg C org ha −1 ) associated with seagrasses along the northern Florida Gulf Coast using field surveys and sediment cores. We measured plant biomass, organic carbon, and sediment composition in each core. Using a multivariate modeling approach, we evaluated the relative importance of ecological, physical, oceanographic, and seascape drivers, developing the first spatially explicit predictions of seagrass‐associated carbon stocks for this region. Applying model predictions to confirmed seagrass beds and potential recovery areas, we also estimated the carbon storage value of potential seagrass conservation and restoration as the resulting stock enhancement value per hectare of seagrass (Δ Mg C org ha −1 ). We found that organic carbon stored by seagrass sediments varied considerably across this region, with stocks significantly increasing with seagrass cover, proximity to oyster reefs, and distance from river outlets, highlighting potential synergies for coordinated management. We also found that current seagrass beds could offer nearly double the carbon storage value of potential recovery areas, emphasizing the importance of conservation as well as restoration. Our results have important implications for management, restoration, and understanding biogeographic patterns of seagrass ecosystem services.

Dynamic behavior of gas-phase NCl3 and CO2 in indoor pool facilities - Lester T. Lee; Tianren Wu; Brandon E. Boor; Ernest R. Blatchley (Building and Environment, 2023)

Diversity in marine protected area regulations: Protection approaches for locally appropriate marine management - Dominic A. Andradi-Brown; Laura Veverka; Amkieltiela; Nicole L. Crane; Estradivari; Helen E. Fox; David Gill; Jordan Goetze; Charlotte Gough; Nils C. Krueck; Sarah E. Lester; Shauna L. Mahajan; et al. (Frontiers in Marine Science, 2023)
Globally, marine protected area (MPA) objectives have increasingly shifted from a primary focus on maintaining ecosystems through prohibiting extractive activities, to more equitable approaches that address the needs of both people and nature. This has led to MPAs with a diverse array of fisheries restrictions and recent debate on the type of restrictions that contribute to achieving biodiversity goals. Here we use a global dataset of 172 MPAs (representing 31 nations) alongside nine detailed case study MPAs (from Australia, Belize, Cambodia, Federated States of Micronesia, Fiji, Indonesia, Madagascar, Solomon Islands, and United States of America), including partially protected areas that allow regulated fishing, to illustrate the many diverse pathways that some MPAs have adopted to protect biodiversity and safeguard the rights and well-being of resource-dependent coastal communities. We group MPAs based on their restrictions and explore four key insights emerging from these groupings using our nine case studies: (i) MPAs use highly diverse approaches to regulate fisheries; (ii) partially protected areas can address gaps in regional fisheries management; (iii) devolving resource management rights to communities influences the chosen fisheries restrictions; and (iv) state-governed MPAs can use highly tailored fisheries restrictions to increase equity in access. We find that partially protected MPAs can offer effective and equitable pathways for biodiversity conservation if tailored to local context. Rather than focusing primarily on fully protected areas for achieving new global MPA targets, we recommend countries use a blend of locally-appropriate protection levels – from fully protected areas to partially protected MPAs to achieve positive biodiversity outcomes.

Recognition of whole-landscape changes due to extreme rain events in a hyperarid desert - Lester Olivares; Teresa E. Jordan; William D. Philpot; Rowena B. Lohman (Remote Sensing Applications: Society and Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Diverse state‐level marine aquaculture policy in the United States: Opportunities and barriers for industry development - Sarah E. Lester; Rebecca R. Gentry; Hayley R. Lemoine; Halley E. Froehlich; Luke D. Gardner; Mae Rennick; Elizabeth O. Ruff; Kimberly D. Thompson (Reviews in Aquaculture, 2022)
Marine aquaculture (mariculture) plays a relatively small role in the United States’ domestic seafood production, despite considerable scope for industry development and high volumes of imported farmed seafood resulting in a significant trade deficit. Currently, most mariculture in the United States occurs in nearshore waters or land‐based tanks and is regulated and guided using state‐level policy, with a relative absence of national coordinating mechanisms to link the patchwork of state policies. There is no comprehensive evaluation showing how different state policies may be enabling or impeding mariculture development. In response, we provide the first systematic overview of state‐level mariculture policy for the 23 coastal marine states in the United States. We compiled information for 16 aquaculture and mariculture policy attributes, including legislation, regulations and management characteristics, particularly those that could enable mariculture development. We found considerable heterogeneity in how states govern and regulate mariculture. As examples, 48% of states have an aquaculture development act, 35% have spatial zoning specifically for mariculture and only 26% have a government‐provided mariculture best management practices document. We examined the relationship between enabling policies and metrics of mariculture output (e.g. production value, number of farms), and while the effect of enabling policy is often equivocal, certain features stand out as important (e.g. government‐provided best management practices). Overall, this policy synthesis suggests approaches that may be influential in enabling mariculture development, which could inform new state‐level policies, an effective overarching federal policy in the United States, or policies in other countries seeking to support an expanded mariculture industry.

How do fisher responses to macroalgal overgrowth influence the resilience of coral reefs? - Andrew Rassweiler; Scott D. Miller; Sally J. Holbrook; Matthew Lauer; Mark A. Strother; Sarah E. Lester; Thomas C. Adam; Jean Wencélius; Russell J. Schmitt (Limnology and Oceanography, 2022)
Many coral reefs have shifted from coral‐ to macroalgae‐dominated community states, heightening the need to understand resilience of coral communities. Fishing on herbivores often reduces resilience of the coral state, as lower herbivory fosters macroalgal establishment. Despite the acknowledged importance of fishing, relatively little attention has been paid to how fishers change their behavior as macroalgae overgrow reefs, or how the resulting dynamic feedbacks might affect resilience. We address these questions in Moorea, French Polynesia, where local fishers target herbivorous fishes and where shifts to algal dominance have occurred on some lagoon reefs. We quantified fisher preferences for reef habitats where they target various taxa. For the two most ecologically important taxa of herbivores targeted in the fishery, parrotfish (Scaridae) and unicornfish ( Naso ), fishers preferred to harvest from locations with less macroalgae. We incorporated these habitat preferences into a spatially explicit social–ecological model of reef dynamics to explore consequences of changes in fishing behavior for resilience of the coral state, particularly following disturbance. Fishing that targets low‐macroalgae locations typically generates resilience by facilitating local recovery of herbivores and thus of coral in the less‐targeted macroalgae‐dominated patches. However, the resulting movement of fishers across the seascape can sometimes create fragility; if coral loss is widespread, avoidance of macroalgae concentrates fishing in patches having the highest coral cover, resulting in loss of coral via reduced herbivory. Our results emphasize that resilience and coral‐macroalgae regime shifts cannot be understood without considering humans as a dynamic part of the system.

Asthma and high-intensity interval training have no effect on clustered cardiometabolic risk or arterial stiffness in adolescents - M. A. McNarry; L. Lester; E. A. Ellins; J. P. Halcox; G. Davies; C. O. N. Winn; K. A. Mackintosh (European Journal of Applied Physiology, 2021)
Purpose Cardiometabolic risk, including arterial stiffness, is increasing in youth. Those with asthma are suggested to be particularly at risk of cardiovascular disease. Efficient and effective strategies are required to prevent the atherosclerotic process in youth. The purpose of this study was to investigate the effect of 6 months high-intensity interval training (HIIT) on cardiometabolic risk in youth with and without asthma. Methods 65 adolescents (31 mild asthma; 34 non-asthma) were recruited, 32 (16 asthma) of whom were randomly allocated to receive HIIT three times per week for 6 months. At baseline, mid-intervention, post-intervention and at a 3-month follow-up, anthropometric, metabolic and vascular determinants of cardiometabolic risk were assessed. Following principal component analysis (PCA), linear mixed models were used to assess the influence of asthma, HIIT and their interaction. Results Seven factors were identified which explained 88% of the common variance shared among the parameters. Those with asthma demonstrated lower arterial stiffness factor scores mid-intervention ( P = 0.047) and lower cholesterol factor scores post-intervention ( P = 0.022) but there was no effect of the intervention, or interaction effects, on any PCA-identified factor, at any time-point. HIIT was associated with a lower low-density lipoprotein and diastolic blood pressure at mid-intervention. Discussion Neither arterial stiffness nor clustered cardiometabolic risk are influenced by HIIT in adolescents with or without asthma, despite important changes in blood lipid and pressure profiles. Blood pressure, augmentation and pulse wave velocity should be considered physiologically distinct constructs and as potential markers of cardiovascular health.

Evaluating the Ecological Benefits of Management Actions to Complement Environmental Flows in River Systems - Sam Nicol; J. Angus Webb; Rebecca E. Lester; Marcus Cooling; Paul Brown; Ian Cresswell; Heather M. McGinness; Susan M. Cuddy; Lee J. Baumgartner; Daryl Nielsen; Martin Mallen-Cooper; Danial Stratford (Environmental Management, 2021)

Basal resource quality and energy sources in three habitats of a lowland river ecosystem - Paul J. McInerney; Galen Holt; Rebecca E. Lester; Ross M. Thompson; Barbara Robson; Darren S. Ryder; Nick R. Bond; Darren S. Baldwin; Ben Gawne; Rochelle Petrie (Limnology and Oceanography, 2020)
Understanding energy flow through ecosystems and among sub‐habitats is critical for understanding patterns of biodiversity and ecosystem function. It can also be of considerable applied interest in situations where managing for connectivity among habitats is important for restoring degraded ecosystems. Here, we describe patterns of basal resource quality and identify primary basal energy sources in three habitats—river channels, anabranches and wetlands—of a lowland river floodplain in the Murray River catchment, Australia during a period of disconnected surface flow. We used a combination of stable isotope and fatty acid analyses to determine which basal resources were assimilated by the backswimmer Anisops thienemanni and the Eastern mosquitofish Gambusia holbrooki and assessed food quality across the three habitats. Seston was a primary basal resource for both animals in all three habitats, but was of higher quality within floodplain habitats than in the river channel. Although floodplain seston contained higher concentrations of essential fatty acids, fatty acid profiles of animals from different habitats remained similar. Our research suggests that inundation of floodplains and subsequent reconnection to the river could be valuable to afford riverine animals the opportunity to access high quality resources, but highlights a need to quantitatively assess the transfer of essential fatty acids between trophic levels to determine how much riverine animals are in fact limited by poorer quality food resources. We demonstrate the importance of estimating the quality of organic matter fluxes into food webs, and the potential role of targeted environmental flows to re‐establish high quality energy pathways in riverine ecosystems.

Caribbean reefs of the Anthropocene: Variance in ecosystem metrics indicates bright spots on coral depauperate reefs - Sarah E. Lester; Andrew Rassweiler; Sophie J. McCoy; Alexandra K. Dubel; Mary K. Donovan; Margaret W. Miller; Scott D. Miller; Benjamin I. Ruttenberg; Jameal F. Samhouri; Mark E. Hay (Global Change Biology, 2020)
Dramatic coral loss has significantly altered many Caribbean reefs, with potentially important consequences for the ecological functions and ecosystem services provided by reef systems. Many studies examine coral loss and its causes—and often presume a universal decline of ecosystem services with coral loss—rather than evaluating the range of possible outcomes for a diversity of ecosystem functions and services at reefs varying in coral cover. We evaluate 10 key ecosystem metrics, relating to a variety of different reef ecosystem functions and services, on 328 Caribbean reefs varying in coral cover. We focus on the range and variability of these metrics rather than on mean responses. In contrast to a prevailing paradigm, we document high variability for a variety of metrics, and for many the range of outcomes is not related to coral cover. We find numerous “bright spots,” where herbivorous fish biomass, density of large fishes, fishery value, and/or fish species richness are high, despite low coral cover. Although it remains critical to protect and restore corals, understanding variability in ecosystem metrics among low‐coral reefs can facilitate the maintenance of reefs with sustained functions and services as we work to restore degraded systems. This framework can be applied to other ecosystems in the Anthropocene to better understand variance in ecosystem service outcomes and identify where and why bright spots exist.

Sleep Disordered Breathing in Hypertrophic Cardiomyopathy - Salma I. Patel; Fadi E. Shamoun; Heidi Esser; Sairam Parthasarathy; Michael J. Ackerman; Jeffrey B. Geske; Steve R. Ommen; William T. Love; Virend K. Somers; Anwar A. Chahal; Johan M. Bos; Stephen S. Cha; et al. (Sleep and Vigilance, 2020)

Spatial Planning Principles for Marine Ecosystem Restoration - Sarah E. Lester; Alexandra K. Dubel; Gema Hernán; Jennifer McHenry; Andrew Rassweiler (Frontiers in Marine Science, 2020)

Roving Divers Surveying Fish in Fixed Areas Capture Similar Patterns in Biogeography but Different Estimates of Density When Compared With Belt Transects - A. Rassweiler; A. K. Dubel; G. Hernan; D. J. Kushner; J. E. Caselle; J. L. Sprague; L. Kui; T. Lamy; S. E. Lester; R. J. Miller (Frontiers in Marine Science, 2020)

Avoidance and aggregation create consistent egg distribution patterns of congeneric caddisflies across spatially variable oviposition landscapes - Jill Lancaster; Barbara J. Downes; Rebecca E. Lester; Stephen P. Rice (Oecologia, 2020)

Perceptions and responses of Pacific Island fishers to changing coral reefs - Andrew Rassweiler; Matthew Lauer; Sarah E. Lester; Sally J. Holbrook; Russell J. Schmitt; Rakamaly Madi Moussa; Katrina S. Munsterman; Hunter S. Lenihan; Andrew J. Brooks; Jean Wencélius; Joachim Claudet (Ambio, 2020)

Projecting marine species range shifts from only temperature can mask climate vulnerability - Jennifer McHenry; Heather Welch; Sarah E. Lester; Vincent Saba (Global Change Biology, 2019)
Climate change is causing range shifts in many marine species, with implications for biodiversity and fisheries. Previous research has mainly focused on how species' ranges will respond to changing ocean temperatures, without accounting for other environmental covariates that could affect future distribution patterns. Here, we integrate habitat suitability modeling approaches, a high‐resolution global climate model projection, and detailed fishery‐independent and ‐dependent faunal datasets from one of the most extensively monitored marine ecosystems—the U.S. Northeast Shelf. We project the responses of 125 species in this region to climate‐driven changes in multiple oceanographic factors (e.g., ocean temperature, salinity, sea surface height) and seabed characteristics (i.e., rugosity and depth). Comparing model outputs based on ocean temperature and seabed characteristics to those that also incorporated salinity and sea surface height (proxies for primary productivity and ocean circulation features), we explored how an emphasis on ocean temperature in projecting species' range shifts can impact assessments of species' climate vulnerability. We found that multifactor habitat suitability models performed better in explaining and predicting species historical distribution patterns than temperature‐based models. We also found that multifactor models provided more concerning assessments of species' future distribution patterns than temperature‐based models, projecting that species' ranges will largely shift northward and become more contracted and fragmented over time. Our results suggest that using ocean temperature as a primary determinant of range shifts can significantly alter projections, masking species' climate vulnerability, and potentially forestalling proactive management.

Short-term accumulation of fauna colonising natural versus artificial seagrass floating near to shore - Ryan J. Baring; Rebecca E. Lester; Peter G. Fairweather (Marine Biology, 2019)

Practical Approaches and Advances in Spatial Tools to Achieve Multi-Objective Marine Spatial Planning - Amanda T. Lombard; Natalie C. Ban; Joanna L. Smith; Sarah E. Lester; Kerry J. Sink; Spencer A. Wood; Aerin L. Jacob; Zacharoula Kyriazi; Richard Tingey; Helena E. Sims (Frontiers in Marine Science, 2019)

Interactions and management for the future of marine aquaculture and capture fisheries - Tyler Clavelle; Sarah E. Lester; Rebecca Gentry; Halley E. Froehlich (Fish and Fisheries, 2019)
Aquaculture surpassed wild fisheries as the largest supplier of fish for human consumption in 2014 and is expected to supply the majority of seafood for future increases in demand. Marine and coastal aquaculture, collectively referred to as mariculture, currently represents just 36% of aquaculture production but is poised to expand in the decades ahead. One of the most commonly cited concerns regarding this likely expansion is ecological and socioeconomic interactions with wild‐capture fisheries. While attention has largely been drawn to high‐profile negative externalities from fed finfish and crustacean mariculture, not all marine‐based practices are equivalent. Empirical evidence for the different interactions between mariculture and wild fisheries is often sparse. While negative consequences can arise, positive synergies can also occur. By considering mariculture development in the context of fisheries interactions, we suggest that it is possible to minimize conflicts and maximize positive connections between the two sectors. We provide the first comprehensive synthesis of the interactions between mariculture and wild fisheries, characterizing the types of interactions, evaluating available empirical evidence and identifying where management (sector‐specific and cooperative) can play an important role. We highlight potential effects of mariculture on the efficiency, sustainability, and equity of seafood production and identify remaining knowledge gaps.

Selecting and applying indicators of ecosystem collapse for risk assessments - Jessica A. Rowland; Emily Nicholson; Nicholas J. Murray; David A. Keith; Rebecca E. Lester; Lucie M. Bland (Conservation Biology, 2018)
Ongoing ecosystem degradation and transformation are major threats to biodiversity. Measuring ecosystem change toward collapse relies on monitoring indicators that quantify key ecological processes. Yet little guidance is available on selection and use of indicators for ecosystem risk assessment. We reviewed indicator use in ecological studies of ecosystem collapse in marine pelagic and temperate forest ecosystems. We examined indicator‐selection methods, indicator types (geographic distribution, abiotic, biotic), methods of assessing multiple indicators, and temporal quality of time series. We compared how these factors were applied in the ecological studies with how they were applied in risk assessments by using the International Union for Conservation of Nature's Red List of Ecosystems (RLE), for which indicators are used to estimate risk of ecosystem collapse. Ecological studies and RLE assessments rarely reported how indicators were selected, particularly in terrestrial ecosystems. Few ecological studies and RLE assessments quantified ecosystem change based on all 3 indicator types, and indicators types used differed between marine and terrestrial ecosystems. Several studies used indices or multivariate analyses to assess multiple indicators simultaneously, but RLE assessments did not because as RLE guidelines advise against them. Most studies and RLE assessments used time‐series data that spanned at least 30 years, which increases the probability of reliably detecting change. Limited use of indicator‐selection protocols and infrequent use of all 3 indicator types may hamper accurate detection of change. To improve the value of risk assessments for informing policy and management, we recommend using explicit protocols, including conceptual models, to identify and select indicators; a range of indicators spanning distributional, abiotic, and biotic features; indices and multivariate analyses with extreme care until guidelines are developed; time series with sufficient data to increase ability to accurately diagnose directional change; data from multiple sources to support assessments; and explicitly reporting steps in the assessment process.

Complex Interactions among Sheep, Insects, Grass, and Fungi in a Simple New Zealand Grazing System - Thomas L. Bultman; Mark R. McNeill; Kelly Krueger; Gina De Nicolo; Alison J. Popay; David E. Hume; Wade J. Mace; Lester R. Fletcher; Yew Meng Koh; Terrence J. Sullivan (Journal of Chemical Ecology, 2018)

Soil organic carbon variability in Australian temperate freshwater wetlands - Alex L. Pearse; Jan L. Barton; Rebecca E. Lester; Atun Zawadzki; Peter I. Macreadie (Limnology and Oceanography, 2018)
Globally, there is little information on freshwater (non‐tidal) wetland below ground soil organic carbon (SOC) stocks, sequestration rates and, in particular, their within‐wetland variation. This basic information is critical for designing programs to sample SOC stocks and identifying areas that sequester large amounts of carbon so that they can be managed to prevent degradation and carbon loss. Here, focusing on temperate seasonally inundated freshwater wetlands in south‐eastern Australia, we compared SOC stocks and sequestration rates (via radiometric dating) among wetlands, within wetland locations (High water mark, Edge and Middle), and with adjacent terrestrial locations. SOC stocks varied most among wetlands but also varied inconsistently within wetlands. Wetland SOC stocks (20.4 ± 0.1 kg C m −2 ) were significantly greater than adjacent terrestrial locations (13.3 ± 0.1 kg C m −2 ). Wetland SOC sequestration rates were similar among all locations (i.e., within a wetland, ranging from 70 g C m −2 yr −1 to 87 g C m −2 yr −1 ). The relative lack of difference in SOC stocks among wetland locations allows for reduced within‐wetland sampling and subsequently greater replication at the wetland level, at least for temperate ephemeral freshwater wetlands, although these findings need to be confirmed over a range of wetland types. This study also produced the first estimates of temperate freshwater wetland SOC stocks and sequestration rates in Australia, and is among the first studies globally to demonstrate that seasonally inundated wetlands can sequester carbon at significant rates. It therefore provides important justification to support the protection and rehabilitation of temperate freshwater wetlands worldwide.

Complex movement patterns by foraging loggerhead sea turtles outside the breeding season identified using Argos‐linked Fastloc‐Global Positioning System - Antoine M. Dujon; Gail Schofield; Rebecca E. Lester; Kostas Papafitsoros; Graeme C. Hays (Marine Ecology, 2018)
We used Argos‐linked Fastloc‐Global Positioning System (Argos‐linked Fastloc‐GPS) satellite tags to investigate how loggerhead sea turtles use neritic foraging habitats at multiple scales. Out of 24 turtles, six individuals used more than one foraging site, with all sites being separated by >25 km. These six individuals used up to four sites, remaining at each site for a mean of 150 days and returning to the same site a minimum of 52 days later. The other 18 turtles remained in a single site. The area within sites was not used uniformly, with 15 out of 24 turtles exhibiting complex movement patterns within and amongst up to five focal patches, which were typically 0.1–5.0 km apart within a single site. Movements between sites and patches might sometimes have reflected overwintering behaviour; however, similar movement patterns occurred at multiple times of the year, suggesting other factors were also involved. Use of multiple sites and patches might be driven by differences in resource availability, such as food and/or night‐time refuges, competition, or exploratory movement to investigate or locate alternative patches. We confirmed competition via direct visual observations of aggressive interactions between individuals at one foraging patch. Our results illustrate the importance of standardizing data to the same number of locations per day and night to accurately delineate key areas used by turtles or for evidence‐based marine protected area planning.

Fastloc-GPS reveals daytime departure and arrival during long-distance migration and the use of different resting strategies in sea turtles - Antoine M. Dujon; Gail Schofield; Rebecca E. Lester; Nicole Esteban; Graeme C. Hays (Marine Biology, 2017)

Hibernation-based blood loss therapy increases survivability of lethal hemorrhagic shock in rats - Cecilia E. Perez de Lara Rodriguez; Lester R. Drewes; Matthew T. Andrews (Journal of Comparative Physiology B, 2017)

Fisheries regulatory regimes and resilience to climate change - Elena Ojea; Isaac Pearlman; Steven D. Gaines; Sarah E. Lester (Ambio, 2017)

Stock assessment in inland fisheries: a foundation for sustainable use and conservation - K. Lorenzen; I. G. Cowx; R. E. M. Entsua-Mensah; N. P. Lester; J. D. Koehn; R. G. Randall; N. So; S. A. Bonar; D. B. Bunnell; P. Venturelli; S. D. Bower; S. J. Cooke (Reviews in Fish Biology and Fisheries, 2016)

Managing Bay and Estuarine Ecosystems for Multiple Services - Lisa A. Needles; Sarah E. Lester; Richard Ambrose; Anders Andren; Marc Beyeler; Michael S. Connor; James E. Eckman; Barry A. Costa-Pierce; Steven D. Gaines; Kevin D. Lafferty; Hunter S. Lenihan; Julia Parrish; et al. (Estuaries and Coasts, 2015)

Population genetic structure of the Australian caddisfly Lectrides varians Mosely (Trichoptera: Leptoceridae) and the identification of cryptic species in south-eastern Australia - S. J. Wickson; E. T. Chester; I. Valenzuela; B. Halliday; R. E. Lester; T. G. Matthews; A. D. Miller (Journal of Insect Conservation, 2014)

Predicting the likely response of data‐poor ecosystems to climate change using space‐for‐time substitution across domains - Rebecca E. Lester; Paul G. Close; Jan L. Barton; Adam J. Pope; Stuart C. Brown (Global Change Biology, 2014)
Predicting ecological response to climate change is often limited by a lack of relevant local data from which directly applicable mechanistic models can be developed. This limits predictions to qualitative assessments or simplistic rules of thumb in data‐poor regions, making management of the relevant systems difficult. We demonstrate a method for developing quantitative predictions of ecological response in data‐poor ecosystems based on a space‐for‐time substitution, using distant, well‐studied systems across an inherent climatic gradient to predict ecological response. Changes in biophysical data across the spatial gradient are used to generate quantitative hypotheses of temporal ecological responses that are then tested in a target region. Transferability of predictions among distant locations, the novel outcome of this method, is demonstrated via simple quantitative relationships that identify direct and indirect impacts of climate change on physical, chemical and ecological variables using commonly available data sources. Based on a limited subset of data, these relationships were demonstrably plausible in similar yet distant (>2000 km) ecosystems. Quantitative forecasts of ecological change based on climate‐ecosystem relationships from distant regions provides a basis for research planning and informed management decisions, especially in the many ecosystems for which there are few data. This application of gradient studies across domains – to investigate ecological response to climate change – allows for the quantification of effects on potentially numerous, interacting and complex ecosystem components and how they may vary, especially over long time periods (e.g. decades). These quantitative and integrated long‐term predictions will be of significant value to natural resource practitioners attempting to manage data‐poor ecosystems to prevent or limit the loss of ecological value. The method is likely to be applicable to many ecosystem types, providing a robust scientific basis for estimating likely impacts of future climate change in ecosystems where no such method currently exists.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Removal Processes for Tributyltin During Municipal Wastewater Treatment - M. D. Scrimshaw; D. Hala; A. E. Okiemute; E. Cartmell; J. N. Lester (Water, Air, & Soil Pollution, 2013)

Transport of Escherichia coli and F-RNA Bacteriophages in a 5-M Column of Saturated, Heterogeneous Gravel - Lester W. Sinton; Margaret L. Mackenzie; Naveena Karki; Rod L. Dann; Liping Pang; Murray E. Close (Water, Air, & Soil Pollution, 2012)

Accuracy of a novel multi-sensor board for measuring physical activity and energy expenditure - Glen E. Duncan; Jonathan Lester; Sean Migotsky; Jorming Goh; Lisa Higgins; Gaetano Borriello (European Journal of Applied Physiology, 2011)

The Pharmaceutical Use of Permethrin: Sources and Behavior During Municipal Sewage Treatment - T. Turner; E. Cartmell; J. N. Lester; F. Casse; S. D. W. Comber; M. D. Scrimshaw (Archives of Environmental Contamination and Toxicology, 2011)

Genotype-dependent effects of adolescent nicotine exposure on dopamine functional dynamics in the nucleus accumbens shell in male and female mice: a potential mechanism underlying the gateway effect of nicotine - Price E. Dickson; Tiffany D. Rogers; Deranda B. Lester; Mellessa M. Miller; Shannon G. Matta; Elissa J. Chesler; Dan Goldowitz; Charles D. Blaha; Guy Mittleman (Psychopharmacology, 2011)

Impact of potassium nutrition on postharvest fruit quality: Melon (Cucumis melo L) case study - Gene E. Lester; John L. Jifon; Donald J. Makus (Plant and Soil, 2010)

A Critical Review of the Formation of Mono- and Dicarboxylated Metabolic Intermediates of Alkylphenol Polyethoxylates during Wastewater Treatment and Their Environmental Significance - T. Y. Chiu; N. Paterakis; E. Cartmell; M. D. Scrimshaw; J. N. Lester (Critical Reviews in Environmental Science and Technology, 2010)

Rehabilitating Agricultural Streams in Australia with Wood: A Review - Rebecca E. Lester; Andrew J. Boulton (Environmental Management, 2008)

Large scale unicoloniality: the population and colony structure of the invasive Argentine ant (Linepithema humile) in New Zealand - S. E. Corin; K. L. Abbott; P. A. Ritchie; P. J. Lester (Insectes Sociaux, 2007)

The relationship between dispersal ability and geographic range size - Sarah E. Lester; Benjamin I. Ruttenberg; Steven D. Gaines; Brian P. Kinlan (Ecology Letters, 2007)
There are a variety of proposed evolutionary and ecological explanations for why some species have more extensive geographical ranges than others. One of the most common explanations is variation in species’ dispersal ability. However, the purported relationship between dispersal distance and range size has been subjected to few theoretical investigations, and empirical tests reach conflicting conclusions. We attempt to reconcile the equivocal results of previous studies by reviewing and synthesizing quantitative dispersal data, examining the relationship between average dispersal ability and range size for different spatial scales, regions and taxonomic groups. We use extensive data from marine taxa whose average dispersal varies by seven orders of magnitude. Our results suggest dispersal is not a general determinant of range size, but can play an important role in some circumstances. We also review the mechanistic theories proposed to explain a positive relationship between range size and dispersal and explore their underlying rationales and supporting or refuting evidence. Despite numerous studies assuming a priori that dispersal influences range size, this is the first comprehensive conceptual evaluation of these ideas. Overall, our results indicate that although dispersal can be an important process moderating species’ distributions, increased attention should be paid to other processes responsible for range size variation.

A decade of the Super Dual Auroral Radar Network (SuperDARN): scientific achievements, new techniques and future directions - G. Chisham; M. Lester; S. E. Milan; M. P. Freeman; W. A. Bristow; A. Grocott; K. A. McWilliams; J. M. Ruohoniemi; T. K. Yeoman; P. L. Dyson; R. A. Greenwald; T. Kikuchi; et al. (Surveys in Geophysics, 2007)

The biogeography of plant reproduction: potential determinants of species’ range sizes - E. Lowry; S. E. Lester (Journal of Biogeography, 2006)
Aim A major biogeographical hypothesis, the ‘niche‐breadth’ hypothesis, explains species range sizes based on the extent of a species’ niche (e.g. diversity of habitats occupied; range of environmental conditions tolerated). An alternative hypothesis explains range sizes using metapopulation theory (e.g. colonization dynamics; dispersal ability). Both niche breadth and colonization ability may be related to plant species’ reproductive characteristics. We evaluate both hypotheses by examining the relationship of plant range size to mating system and genomic structure (ploidy status). Location Western North America. Methods Using a data set of 60 taxa in the genus Clarkia (Onagraceae), we use three analytical techniques to examine the effect of reproductive characteristics on range size. We conduct cross‐species analyses of present‐day taxa to examine both mating system and polyploidy in relation to range size. We also conduct a phylogenetically independent contrasts analysis (using caic software) on the relationship of mating system to range size in diploid species. Third, we compare closely related taxon pairs that differ in mating system as an alternative method to control for phylogeny. Results Polyploid species have significantly larger ranges compared with diploid species. When considering only diploid taxa, no significant relationship is found for mating system in both cross‐species and phylogenetically independent contrasts analyses. The diploid pairwise analysis, comparing only the range sizes of direct sister taxa with alternative mating systems, does show a relationship, with outcrossing species having larger ranges than self‐fertilizing species. Main conclusions We argue that genetic diversity, colonization ability, or a combination of both factors may influence plant species’ range sizes. The significant pairwise analysis suggests that both the independent contrast and the cross‐species analysis may be confounded by polytomies of species at the terminal nodes of the phylogeny, indicating the importance of comparing the results of multiple analytical techniques. We propose that the range sizes of self‐fertilizing species have a bimodal distribution, obscuring the effect of mating system on range size, and that a broader survey of plant taxa will resolve the two modes from that of the outcrossing species. Lastly, polyploid species appear to show significantly larger range sizes than diploid species, irrespective of mating system.

Stock structure of Spanish mackerel Scomberomorus commerson along the Australian east coast deduced from parasite data - R. E. Williams; R. J. G. Lester (Journal of Fish Biology, 2006)
The parasite fauna of Spanish mackerel Scomberomorus commerson from three regions off eastern Australia was examined for evidence of separate stocks. The abundance of five metacestodes was very similar in all areas suggesting that extensive mixing of the fish occurs along the coast, unlike the situation across northern Australia where large differences have been found between regions. The similarity in abundances of two metacestodes from Townsville fish and south‐east Queensland fish suggests that these two regions have fish with very similar histories. The data lead to the conclusion that the seasonal fishery for Spanish mackerel off south‐east Queensland is based on a random group of fish from the same origin as fish sampled off Townsville and is not a subpopulation that moves south each year.

Responses of Female Orange Wheat Blossom Midge, Sitodiplosis mosellana, to Wheat Panicle Volatiles - Michael A. Birkett; Toby J. A. Bruce; Janet L. Martin; Lesley E. Smart; Jon Oakley; Lester J. Wadhams (Journal of Chemical Ecology, 2004)

Near-infrared spectral imaging for quality assurance of pharmaceutical products: Analysis of tablets to assess powder blend homogeneity - Robbe C. Lyon; David S. Lester; E. Neil Lewis; Eunah Lee; Lawrence X. Yu; Everett H. Jefferson; Ajaz S. Hussain (AAPS PharmSciTech, 2002)

Estimation of genetic parameters in a recurrent selection program in Apple - Nnadozie C. Oraguzie; Madeleine E. Hofstee; Lester R. Brewer; Craig Howard (Euphytica, 2001)

Age-specific Effects of Novel Mutations in Drosophila Melanogaster II. Fecundity and Male Mating Ability - Paul D. Mack; Vanessa K. Lester; Daniel E. L. Promislow (Genetica, 2000)

AFLP analysis of genetic relationships in the tribe Datureae (Solanaceae) - E. S. Mace; C. G. Gebhardt; R. N. Lester (Theoretical and Applied Genetics, 1999)

AFLP analysis of genetic relationships among the cultivated eggplant, Solanummelongena L., and wild relatives (Solanaceae) - E. S. Mace; R. N. Lester; C. G. Gebhardt (Theoretical and Applied Genetics, 1999)

Evaluation of Olfactory Sensing in the Water Industry - R. E. H. Sweeney; M. D. Scrimshaw; G. K. Morse; J. N. Lester (Environmental Monitoring and Assessment, 1998)